Analisis Linguistik Terminologi Fiqh Muamalah dalam Kontrak Keuangan Syariah Modern: Implikasi untuk Pendidikan Bahasa Arab dan Literasi Ekonomi Syariah: Implikasi untuk Pendidikan Bahasa Arab dan Literasi Ekonomi Syariah - Slamet Riyadi; Hasugian, Dirja; Andri Rivai (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
This study aims to examine students' understanding of fiqh muamalah terminology in the context of modern Islamic finance. Through a qualitative analysis of survey data collected from students, this study found that the majority of students have a good understanding of fiqh muamalah terms commonly used in Islamic financial transactions. However, there is still a gap in understanding of some more specific terms. The study also showed a positive correlation between proficiency in Arabic and the ability to understand fiqh muamalah terminology. The findings of this study have important implications for the development of Islamic education curricula and the improvement of human resources in the Islamic finance industry.